Caracterização da pulverização pneumática em cafeeiro conilon - Canal, Luciano. (2016)
The rust of coffee is a major disease of culture and constitutes a limiting factor for causing the premature fall of diseased leaves, affecting flowering and fruiting and hence future production. The most widely used measure of management for the control of rust and applying fungicides, triazoles and basically strobilurins. Not enough to know the nature of the plant protection product, it is also necessary to use the best available technology in order to ensure an efficient implementation. There is a growing use of tractor-implement pneumatic sprays the coffee plantations of Espirito Santo north due to densification of the plantations, the fall of orthotropic branches by weight of fruit production and the need for emergency interventions. There are some questions about the gun type spray application efficiency in coffee plantations, many without any scientific basis. The aim of this study was to evaluate the efficacy of chemical control of rust in coffee Conilon by the scope of the jet sprayed by equipment type cannon. The experiment was installed in a property of the municipality of Vila Valério-ES, and rust evaluated in a Conilon coffee plantation in full sun with 9 years of age with localized irrigation and productivity of 105 ha-1 bags in 2015 and organized 3 lines 'clone 02' alternating with 1 line of clonal selection G35, with plant spacing of 3.60 x 1.20 m. Data were collected from April to July 2015 in genotype plants 02. The application of the fungicide was held on 11.04.2015 and, for this operation, was made a single pass of the tractor-sprayer set on the side of the experimental area parallel to the lines of planting, using tractor Valtra BF75 with vm displacement of 4.8 km h-1, and coupled with this, a pneumatic spray J600 company jet, equipment type cannon that allows in favorable wind conditions, reach up to 35.0 m swath. The experimental design (CRD) consisted of 6 treatments, 5 repetitions and parcel consisting of 10 useful plants. Each treatment corresponded to a line of coffee 'Clone 02', starting from the nearest line passing a tractor sprayer set to a distance of 21.60 m. The evaluation of the incidence of rust was made monthly through destructive sampling, where six leaves per plant were taken at random from the 3rd or 4th pair of fully developed leaves from the end of the reproductive branches of median canopy region. In conclusion: the application with pneumatic spray was effective in the first lines of planting, reaching a distance of 14.40 m; it is necessary to overlap the application, using a corresponding application range 50% of the maximum spray range; it is feasible to use the pneumatic spray gun type for control of coffee rust, since the technical criteria for efficient application are met, it should be recommended for large areas with dense plantings in coffee preharvest stage and in case the need for emergency applications.